Armodafinil versus Modafinil in Patients of Excessive Sleepiness Associated with Shift Work Sleep Disorder: A Randomized Double Blind Multicentric Clinical Trial - D. V. Tembe; A. Dhavale; H. Desai; D. N. Mane; S. K. Raut; G. Dhingra; U. Sardesai; S. Saoji; M. Rohra; V. G. Shinde; M. Padsalge; A. Paliwal; et al. (Neurology Research International)
Aim. To compare the efficacy and safety of armodafinil, the R-enantiomer of modafinil, with modafinil in patients of shift work sleep disorder (SWSD). Material and Methods. This was a 12-week, randomized, comparative, double-blind, multicentric, parallel-group study in 211 patients of SWSD, receiving armodafinil (150 mg) or modafinil (200 mg) one hour prior to the night shift. Outcome Measures. Efficacy was assessed by change in stanford sleepiness score (SSS) by at least 2 grades (responder) and global assessment for efficacy. Safety was assessed by incidence of adverse events, change in laboratory parameters, ECG, and global assessment of tolerability. Results. Both modafinil and armodafinil significantly improved sleepiness mean grades as compared to baseline (𝑃<.0001). Responder rates with armodafinil (72.12%) and modafinil (74.29%) were comparable (𝑃=.76). Adverse event incidences were comparable. Conclusion. Armodafinil was found to be safe and effective in the treatment of SWSD in Indian patients. The study did not demonstrate any difference in efficacy and safety of armodafinil 150 mg and modafinil 200 mg.